2020
DOI: 10.1093/eurpub/ckaa179
|View full text |Cite
|
Sign up to set email alerts
|

Coverage rates against vaccine-preventable diseases among healthcare workers in Sicily (Italy)

Abstract: Background Vaccination of healthcare workers (HCWs) reduces the risk of occupational vaccine-preventable diseases (VPDs), prevents their nosocomial transmission and preserves healthcare delivery during outbreaks. Extensive implementation of vaccination programmes for HCWs allowed the elimination or control of several VPDs within healthcare facilities; despite these, the vaccine adherence rates among HCWs are persistently suboptimal. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…All HCP must be skilled in occupational exposure risks and preventive and protective procedures. Furthermore, previous studies in the same Italian hospital have shown their low vaccination coverage for VPDs [ 9 , 22 , 23 , 24 , 26 , 28 ]. This exposes themselves and their patients to VPDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All HCP must be skilled in occupational exposure risks and preventive and protective procedures. Furthermore, previous studies in the same Italian hospital have shown their low vaccination coverage for VPDs [ 9 , 22 , 23 , 24 , 26 , 28 ]. This exposes themselves and their patients to VPDs.…”
Section: Discussionmentioning
confidence: 99%
“…One group intended for priority vaccination is healthcare personnel (HCP). Studies have shown significant gaps in knowledge towards VPDs and vaccines among HCP and, therefore, vaccination uptake rates among them [ 8 , 9 ]. This lack of HCP compliance towards vaccinations contributes to vaccine hesitancy, which detracts from vaccination programs’ effectiveness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is an important means to prevent the occurrence and spread of serious infectious diseases and related complications [47]. HCWs have a high risk of exposure and are also the main means of transmission and spread of infections in hospitals, due to their contact with patients [48].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the total protection of a pregnant woman, strategies that can involve the vaccination of figures who are most in contact with her (e.g., partners) should be selected, giving the possibility to perform the 10-year booster dose of vaccination in case the booster has not been administered in the last decade [ 61 , 62 ].…”
Section: Importance Of Vaccination For a Pregnant Woman And Strategie...mentioning
confidence: 99%